First experience of transcatheter implantation of a Russian-made MedLab-CT prosthesis in a patient with dysfunction of biological mitral valve prosthesis - A. V. Bogachev-Prokofiev; R. M. Sharifulin; M. A. Ovcharov; A. N. Pivkin; O. V. Krestyaninov; T. V. Antropova; M. A. Ovchinnikova; D. A. Astapov; A. V. Sapegin; A. V. Afanasyev; S. A. Budagaev; S. I. Zheleznev (Российский кардиологический журнал)
We present a case report of successful transcatheter implantation of a Russian-made cardiac valve prosthesis in a patient with dysfunction of biological mitral valve prosthesis (valve-in-valve). A patient aged 78 years with a high surgical risk and severe heart failure due to mitral valve bioprosthesis dysfunction is described. Fluoroscopyand transesophageal echocardiography-guided transapical implantation of a MedLab-CT prosthesis (23 mm) was made. When a heart rate of 180 beats per minute, a stent prosthesis was implanted. Transcatheter implant valve functioned properly after surgery. The patient was discharged in satisfactory condition.